The Effect of Market Segmentation and Customer Preference on Customer Satisfaction of Ice Cream Mixue in Yogyakarta - Teguh Setiawan Wibowo; Jaka Sudewa; Dwi Novaria Misidawati; Puji Afriyeni; Normansyah Normansyah; Muhammad Rizki (International Journal of Economics Development Research (IJEDR), 2023)
The things that are important and need to be considered in marketing the products to be sold are by analyzing market segmentation and understanding customer needs and wants. This is what Ice Cream Mixue does in Yogyakarta in formulating its marketing strategy in facing market share competition with its competitors. The purpose of this study was to analyze the effect of Market Segmentation and Customer Preferences on Customer Satisfaction of Ice Cream Mixue in Yogyakarta. Data analysis techniques using Partial Least Square (SEM-PLS). The sample in this study were 65 customers who were Ice Cream Mixue connoisseurs who had bought and consumed it regularly which were taken randomly for outlets in the city of Yogyakarta which were spread across 5 branches.The results showed that market segmentation and customer preferences had a positive and significant effect on customer satisfaction with an original sample value of 0.456; 0.417 and a p-value of 0.001; 0.002 with a standard error of 5%. These results indicate that if market segmentation is formed correctly and customer preferences are met, it can affect the high customer satisfaction at ice cream mixue outlets in Yogyakarta.